Generational shift in melanoma incidence and mortality in Queensland, Australia, 1995–2014. Issue 8 (21st November 2017) - Aitken, Joanne F.; Youlden, Danny R.; Baade, Peter D.; Soyer, H. Peter; Green, Adèle C.; Smithers, B. Mark
Abstract : Public campaigns encouraging sun protection for skin cancer prevention began in Queensland, Australia, in the early 1980s. We examined recent trends to assess whether earlier evidence of stabilizing melanoma incidence in young people has persisted. Anonymized incidence and mortality data for in situ and invasive melanoma for the 20 years 1995–2014 were obtained from the Queensland Cancer Registry. Time trends were analyzed using JoinPoint regression. Birth cohort patterns were assessed using age–period–cohort models. Melanoma incidence in Queensland remains the highest recorded in the world (age‐standardized incidence of invasive melanoma (2010–2014) = 72/100, 000/annum). Over the 20‐year period, incidence of in situ melanoma increased in all age groups. Incidence of both thin (≤1 mm) and thick (>1 mm) invasive melanoma was either stable or decreased in people under 60, while it increased in those aged 60 and above, particularly in men. Age–period–cohort analysis revealed decreasing age‐specific incidence of invasive melanoma under 40 years of age, beginning with the birth cohort born around the mid‐1960s, with steepest falls for those born around 1980 and later. Age‐specific incidence was stable between 40 and 59 years of age from the 1945 birth cohort onwards. Melanoma mortality over the period was stable or decreased in all groups except in men aged 60 or over. These findings are evidence of real advances in the prevention and early detection of invasive melanoma in this very high‐risk population. They make a compelling case for continued public health efforts to reduce the burden of melanoma in susceptible populations. Abstract : What's new? Queensland, Australia has long had the highest recorded melanoma incidence in the world, with public campaigns encouraging sun protection for skin cancer prevention beginning in the early 1980s. Here, the authors examined recent trends to assess whether earlier evidence of stabilizing melanoma incidence in young people has persisted. They show that rates of invasive melanoma have peaked over the last two decades for persons aged under 60. Coupled with stable or declining mortality rates, except in men over 60, the results provide substantive evidence that long‐running melanoma prevention and early‐detection campaigns have reduced the burden of melanoma across successive generations.